2008
DOI: 10.1016/j.cub.2008.01.063
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Variance in Life-History Strategies within Invasive Populations by Way of Multiple Introductions

Abstract: Biological invasions represent major threats to biodiversity as well as large-scale evolutionary experiments. Invasive populations have provided some of the best known examples of contemporary evolution [3-6], challenging the classical view that invasive species are genetically depauperate because of founder effects. Yet the origin of trait genetic variance in invasive populations largely remains a mystery, precluding a clear understanding of how evolution proceeds. In particular, despite the emerging molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
270
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(283 citation statements)
references
References 25 publications
7
270
2
4
Order By: Relevance
“…When adaptive variants from a genetically distinct population introgress, natural selection can act on this enhanced standing variation without waiting for new mutations to arise de novo [57]. For these reasons, and because invasive species frequently experience novel selective environments in their introduced range, admixture has been implicated as a potential factor fuelling rapid evolution and the generation of novel invasive genotypes [33,48,58]. Nevertheless, direct evidence of a link between introgressed variation and the evolution of invasiveness is largely lacking to date.…”
Section: (C) the Pros And Cons Of Genetic Admixturementioning
confidence: 99%
“…When adaptive variants from a genetically distinct population introgress, natural selection can act on this enhanced standing variation without waiting for new mutations to arise de novo [57]. For these reasons, and because invasive species frequently experience novel selective environments in their introduced range, admixture has been implicated as a potential factor fuelling rapid evolution and the generation of novel invasive genotypes [33,48,58]. Nevertheless, direct evidence of a link between introgressed variation and the evolution of invasiveness is largely lacking to date.…”
Section: (C) the Pros And Cons Of Genetic Admixturementioning
confidence: 99%
“…Invasive species can also trigger horizontal reorganizations of food webs, by altering competitive relationships between species at the same trophic level through competition for resources, apparent (i.e., predator‐mediated), or interference competition. Such horizontal reorganizations may even lead to successions of invaders, with each new invader replacing the previous one as the dominant species (Facon, Pointier, Jarne, Sarda, & David, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Several population genetic studies have revealed mixed ancestries of invasive populations reflecting genetic admixture of multiple divergent native source populations (e.g., Kolbe et al., 2004; Rosenthal, Ramakrishnan, & Cruzan, 2008; Chun, Fumanal, Laitung, & Bretagnolle, 2010; Stephen R. Keller, Gilbert, Fields, & Taylor, 2012). Moreover, some studies also provide evidence for phenotypic changes and effects on fitness associated with admixture (Kolbe, Larson, & Losos, 2007; Facon, Pointier, Jarne, Sarda, & David, 2008; S. R. Keller & Taylor, 2010). However, although these observational studies suggest a strong link of genetic admixture and invasion success, it remains difficult to disentangle the direct effects of genetic admixture (e.g., heterosis) from long‐term effects of increases in genetic variation (evolutionary potential), as well as other confounding effects such as propagule pressure that may be associated with multiple introductions.…”
Section: Introductionmentioning
confidence: 99%